Comparison of Tripterygium wilfordii Hook F with methotrexate in the treatment of active rheumatoid arthritis (TRIFRA): a randomised, controlled clinical trial. Issue 6 (14th April 2014) - Lv, Qian-wen; Zhang, Wen; Shi, Qun; Zheng, Wen-jie; Li, Xin; Chen, Hua; Wu, Qing-jun; Jiang, Wan-lan; Li, Hong-bin; Gong, Lu; Wei, Wei; Liu, Hui; et al.
Abstract : Objectives: To compare the efficacy and safety of Tripterygium wilfordii Hook F (TwHF) with methotrexate (MTX) in the treatment of active rheumatoid arthritis (RA). Methods: Design: a multicentre, open-label, randomised controlled trial. All patients were assessed by trained investigators who were unaware of the therapeutic regimen. Intervention: 207 patients with active RA were randomly allocated (1:1:1) to treatment with MTX 12.5 mg once a week, or TwHF 20 mg three times a day, or the two in combination. At week 12, if reduction of the 28-joint count Disease Activity Score (DAS28) was <30% in the monotherapy groups, the patient was switched to MTX+TwHF. The primary efficacy point was the proportion of patients achieving an American College of Rheumatology (ACR) 50 response at week 24. Results: 174/207 (84.1%) patients completed 24 weeks of the trial. In an intention-to-treat analysis, the proportion of patients reaching the ACR50 response criteria was 46.4% (32/69), 55.1% (38/69) and 76.8% (53/69), respectively, in the MTX, TwHF and MTX+TwHF groups (TwHF vs MTX monotherapy, p=0.014; MTX+TwHF vs MTX monotherapy, p<0.001). Similar statistically significant patterns at week 24 were found for ACR20, ACR70, clinical Disease Activity Index good responses, EULAR good response, remission rate and low disease activity rate. Significant improvement in the Health Assessment Questionnaire and 36-item Short-Form Health Survey questionnaire scores from baseline to week 24 was seen in each treatment arm (p<0.05), though no significant difference was found among the treatment arms (p>0.05). The result of per-protocol analysis agreed with that seen in the intention-to-treat analysis. Seven, three and five women in the TwHF, MTX and combination groups, respectively, developed irregular menstruation (TwHF vs MTX monotherapy, p=0.216). Conclusions: TwHF monotherapy was not inferior to, and MTX+TwHF was better than, MTX monotherapy in controlling disease activity in patients with active RA. Trial registration number: NCT01613079.